Disease in the vegetable kingdom - Thompson, Charles Henry (My University, 1893)
Introduction: My object in presenting this compilation and original research on a subject of so great importance to the agricultural and horticultural waves of today is not to give a full knowledge of the innumerable diseases affecting plant life, nor give a definite understanding of any one class of such diseases, but my object is to present the subject in a very general way so that one may be better qualified to recognize as diseases many derangements in plant growth which now he beholds vaguely and passes by with no further knowledge of the nature of such deformations.
Citation: Thompson, Charles Henry. Disease in the vegetable kingdom. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Agriculture; Horticulture; Disease; Plant life; Theses; Manuscripts (documents)